Recommendations for long-term home oxygen therapy in children and adolescents - Fabíola V. Adde; Alfonso E. Alvarez; Beatriz N. Barbisan; Bianca R. Guimarães (Brazilian Society of Pediatrics, 2013)
Objective: To advise pediatricians, neonatologists, pulmonologists, pediatric pulmonologists, and other professionals in the area on the main indications and characteristics of long-term home oxygen therapy in children and adolescents. Data source: A literature search was carried out in the MEDLINE/PubMed database (1990 to 2011). Additionally, references from selected studies were included. As consistent scientific evidence does not exist for many aspects, some of the recommendations were based on clinical experience. Data synthesis: Long-term home oxygen therapy has been a growing practice in pediatric patients and is indicated in bronchopulmonary dysplasia, cystic fibrosis, bronchiolitis obliterans, interstitial lung diseases, and pulmonary hypertension, among others. The benefits are: decrease in hospitalizations, optimization of physical growth and neurological development, improvement of exercise tolerance and quality of sleep, and prevention of pulmonary hypertension/cor pulmonale. The levels of oxygen saturation indicative for oxygen therapy differ from those established for adults with chronic obstructive pulmonary disease, and vary according to age and disease. Pulse oximetry is used to evaluate oxygen saturation; arterial blood gas is unnecessary. There are three available sources of oxygen: gas cylinders, liquid oxygen, and oxygen concentrators. The flows used are usually smaller, as are the number of hours/day needed when compared to the use in adults. Some diseases show improvement and oxygen therapy discontinuation is possible. Conclusions: Long-term home oxygen therapy is increasingly common in pediatrics and has many indications. There are relevant particularities when compared to its use in adults, regarding indications, directions for use, and monitoring.